1994
DOI: 10.1002/jbm.820280508
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of carcinogenicity and chronic toxicity associated with orthopedic implants in mice

Abstract: The carcinogenicity and chronic toxicity of 316L stainless steel, nickel, Ti-6A1-4V, hydroxyapatite (HA)-coated Ti-6A1-4V, aluminum oxide containing yttrium oxide, and zirconium oxide containing yttrium oxide were evaluated by implanting solid rods of each material in the thigh muscle of C57BL/6N mice for 24 months. Nickel alloy showed high carcinogenic and toxic potencies, whereas other materials showed no evidence of them. Tumors retaining nickel alloys were malignant fibrous histiocytoma or fibrosarcoma. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(56 citation statements)
references
References 31 publications
1
52
0
3
Order By: Relevance
“…These metallic ions pose a potential health hazard capable of inducing allergic reactions or even promoting the onset of cancer. [17][18][19] Several researches had previously investigated the selective leaching behaviour of TiNi and TiNiCu SMAs [20][21][22][23] ; however, the selective leaching of Ti, Ni, and Fe ions released from TiNiFe SMAs has not been studied. Therefore, this study investigated the selective leaching and surface properties of Ti 50 Ni 50-x Fe x (x = 1, 2, and 3) SMAs using inductively coupled plasma mass spectrometry (ICP-MS), an X-ray diffraction (XRD) analysis, electrochemical tests, and X-ray photoelectron spectroscopy (XPS).…”
Section: Introductionmentioning
confidence: 99%
“…These metallic ions pose a potential health hazard capable of inducing allergic reactions or even promoting the onset of cancer. [17][18][19] Several researches had previously investigated the selective leaching behaviour of TiNi and TiNiCu SMAs [20][21][22][23] ; however, the selective leaching of Ti, Ni, and Fe ions released from TiNiFe SMAs has not been studied. Therefore, this study investigated the selective leaching and surface properties of Ti 50 Ni 50-x Fe x (x = 1, 2, and 3) SMAs using inductively coupled plasma mass spectrometry (ICP-MS), an X-ray diffraction (XRD) analysis, electrochemical tests, and X-ray photoelectron spectroscopy (XPS).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the fact that Ti-Ni contains approximately 50% nickel, which is considered a toxic and even carcinogenic element, represents the strongest argument against its use as an implant material because of a possible release of nickel in the human body and the potential danger to a patient's overall health [3].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the replacement of metal by zirconia did not produce noticeable changes in the cellular response to the inserts. Previous work has shown the safety, biocompatibility and stability of zirconia ceramics (17)(18)(19), and the lack of mutagenic and carcinogenic effect (20).…”
Section: Discussionmentioning
confidence: 99%